2017
DOI: 10.3892/etm.2017.4702
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-33b inhibits cell proliferation and glycolysis by targeting hypoxia-inducible factor-1α in malignant melanoma

Abstract: Malignant melanoma (MM) is the most aggressive type of skin cancer. MicroRNA (miR) has been implicated in the development and progression of MM; however, their underlying mechanism of action remains largely unknown. The present study aimed to investigate the role of miR-33b in MM. Reverse transcription-quantitative polymerase chain reaction data indicated that the expression of miR-33b was significantly reduced (P<0.01) in MM cell lines, including WM35, WM451 and SK-MEL-1, when compared with human melanocyte c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…26,27 Further, we showed that miR-33b overexpression attenuated the proliferation, colony formation of NSCLC cells and promoted cell cycle arrest and apoptosis ( Figure 2). Currently, surgery is the primary treatment modality for NSCLC patients in stage I, II &III.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…26,27 Further, we showed that miR-33b overexpression attenuated the proliferation, colony formation of NSCLC cells and promoted cell cycle arrest and apoptosis ( Figure 2). Currently, surgery is the primary treatment modality for NSCLC patients in stage I, II &III.…”
Section: Discussionmentioning
confidence: 94%
“…LDHA is an enzyme of the glycolytic pathway, which plays a role in the regulation of glycolysis in anaerobic conditions. 26 Notably, miR-33b also regulates the metabolism of fatty acids, 35 and other cancer-related processes, such as angiogenesis, hypoxia, etc., which presumably all contribute to the tumor-attenuation effects of miR-33b. 32 In our study, the interaction between LDHA and miR-33b was verified by luciferase reporter assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although changes in metabolites can regulate cellular metabolism, genes, and related signaling pathways also affect metabolic processes in cancer cells [25,26]. The Akt/HIF signaling pathway regulates aerobic glycolysis through transcriptional activation of HIF1α, NFκB, c-myc, and the subsequent expression of glycolytic enzymes such as hexokinase 2 (HK2), phosphofructokinase 2 (PFK2), and pyruvate kinase isozyme type M2 (PKM2) [27][28][29][30][31]. In our research, we found OA inhibited the expression of glycolytic enzymes through inhibition of the Akt/HIF signaling pathway.…”
Section: Introductionmentioning
confidence: 99%